Productive Efficiency and Non-performing Assets of Indian Banks in the Post-global Financial Crisis Period. Issue 2 (September 2021) - Khati, Karan Singh; Mukherjee, Deep
This study endeavours to augment the existing literature on the productive efficiency of Indian domestic banks in the presence of non-performing assets (NPAs), by employing the Weighted Russell Directional Distance Model (WRDDM). Following the intermediation approach, the banking technology set includes three inputs, three desirable outputs and one undesirable output, namely NPAs. Due to their inherent technological heterogeneity, public sector banks (PSBs) and private banks (PVBs) have been analysed as separate groups. Balanced panels of 26 PSBs and 18 PVBs are constructed from 2010-2011 to 2016-2017. The results indicate a considerable scope of improvement in the productive performance of both categories of banks. The break-up of overall inefficiency into input- and output-specific components reveals some stimulating information. For PSBs, the inefficiencies primarily result due to physical capital, while for PVBs they emerge mainly from other incomes. However, NPAs are also a key contributor to inefficiency for both the categories of banks. The inefficiency scores also indicate that, across ownership categories, medium-sized banks are poorer performers than their smaller and larger counterparts. JEL: C14, C61, D24, G21